View of inner dome from lobby - Ghosh, Ayan (Jio Institute, 2023)
Frederick Stevens incorporated a double dome inside the main tower of the BMC building. The outer dome is visible from the street, but the inner dome is visible only from the entrance hall when the visitor looks up. The inner dome was inspired by the Gol Gumbaz at Bijapur. However, spanning just 45 feet in diameter, the inner dome is much smaller in scale compared to the Gol Gumbaz, which is the largest unsupported dome in India.